The Comparison of Ostecytein the Pressure area and Tension area on Tooth Movement Because of Hyperbaric Oxygen Therapy - Muhammad Faizal Winaris; Arya Brahmanta; Pambudi Raharjo (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Orthodontic tooth movement is a interaction prosess of resorption and deposition of bone remodeling. Orthodontic tooth movement by mechanical strength causes changes in alveolar bone. Osteocyte is an essential cell to respond bone remodelling. Hyperbaric Oxygen Therapy affects production of osteocyte because it can release Reactive Oxygen Species (ROS) and Nitrid Oxide (NO). Purpose: To determine the difference number of osteocyte in pressure and tension area during tooth movement by adjuvant of Hyperbaric Oxygen 2,4 ATA during 7 days starting on day 8 to day 14. Materials and Methods: This research used Completery Randomized Control Group Post Test Only Design. 36 cavia cobaya (male) were divided into 3 groups randomly : the negative control groups, positive control group, and treatment group. Preparat staining used Hematoxylin Eosin (HE) and calculated on microscop 1000x with 20 field of view. Data analyses used one way ANOVA and LSD test then compared each area by using paired T test. Result: The data showed that the treatment group (P=10,67) tension area has the highest number of osteocyte than negative control group (K-=3,67), positive control (K+=7,42). In the pressure area showed that negative control group (K-=5,00) has the highest than positive control group (K+=3,83) and treatment (P=3,25). Conclusion: Therapy HBO 2,4 ATA 7 days starting on day 8 to day 14 is could increase osteocyte in the tissue to stimulate process of bone remodelling.